2016
DOI: 10.1167/iovs.15-18658
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Attenuates Retinal Inflammation and Protects Blood–Retinal Barrier in Diabetic Rats

Abstract: Citation: Fan L, Yan H. FTY720 attenuates retinal inflammation and protects blood-retinal barrier in diabetic rats. Invest Ophthalmol Vis Sci. 2016;57:125457: -126357: . DOI:10.1167 PURPOSE. FTY720 has shown a protective effect in several diseases via inhibiting inflammation and decreasing vascular permeability. The purpose of this study was to assess the impact of FTY720 on inflammation and the blood-retinal barrier (BRB) in diabetic rats.METHODS. Male Wister rats were induced to develop diabetes by streptoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Owing to the fact that continuous treatment with fingolimod decreases surface expression of the S1P 1 receptor and that S1P 2 /S1P 3 activation increases endothelial barrier permeability [62], one possible explanation for the development of ME might be a shift of the balance from S1P 1 towards S1P 2 /S1P 3 signaling resulting in the activation of Rho/ROCK signaling pathways [62]. However, in one recent study, attenuation of retinal vascular leakages after a 12-week fingolimod treatment in streptozotocin (STZ)-induced diabetic rats has been reported [63]. Moreover, there are several works underlining that long-term treatment with fingolimod does not impair endothelial barrier function [64,65], which might be explained by the fact that, despite membrane downregulation, the internalized S1P 1 receptor still actuates signaling pathways [66] or that this function does not depend on the S1P 1 receptor at all [67].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the fact that continuous treatment with fingolimod decreases surface expression of the S1P 1 receptor and that S1P 2 /S1P 3 activation increases endothelial barrier permeability [62], one possible explanation for the development of ME might be a shift of the balance from S1P 1 towards S1P 2 /S1P 3 signaling resulting in the activation of Rho/ROCK signaling pathways [62]. However, in one recent study, attenuation of retinal vascular leakages after a 12-week fingolimod treatment in streptozotocin (STZ)-induced diabetic rats has been reported [63]. Moreover, there are several works underlining that long-term treatment with fingolimod does not impair endothelial barrier function [64,65], which might be explained by the fact that, despite membrane downregulation, the internalized S1P 1 receptor still actuates signaling pathways [66] or that this function does not depend on the S1P 1 receptor at all [67].…”
Section: Discussionmentioning
confidence: 99%
“…These results agreed with many studies (Giurdanella et al 2017) (Saker et al 2014), who postulated that AGE were localized to retinal blood vessels in diabetics and were correlated with the degree and clinical progression of retinopathy. (Giurdanella et al 2017) and (Saker et al 2014) found that AGE were elevated in various ocular tissues of diabetic subjects compared to diabetics without retinopathy (Navaratna et al 2007) (Fan and Yan 2016).This includes vitreous collagen (Fan and Yan 2016), where the AGE levels correlate with diabetic retinopathy (Kim et al There was no significant difference in the genotype distribution (C/C, C/G, G/G) of the C˗1214G polymorphism between the two groups of patients with and without DR. Also, there was no significant difference of G and C allele frequencies Fig. 1 Genotypes of the C/G polymorphism at the -1214-bp SDH promoter region determined by allele-specific PCR detection (ASO-PCR) and analyzed by 2% agarose gel electrophoresis, stained with ethidium bromide, and viewed under gel documentation system.…”
Section: Discussionmentioning
confidence: 99%
“…Adherens junctions (AJ) are mediated by VE-cadherin which promotes Ca 2+ -dependent homophilic cell to cell contacts, and interact intracellularly with actin cytoskeleton through catenins [36], while AGEs stimulation resulted in cleavage of VE-cadherin from the cell surface [39]. Treatments regarding to restore the expression of junction proteins are able to protect RECs from hyperglycemic insult to maintain their barrier properties [38,40]. Signaling events downstream of the AGE-RAGE pathway that dysregulate the junctional molecules were demonstrated in the last few years but still remained to be determined.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…This conception was supported by the clinical results from Hoorn Study, a population-based cohort study, which recruited 625 patients and suggested that the prevalence of retinopathy was positively associated with tertiles of C reactive protein (CRP) and soluble intercellular cell adhesion molecule 1 (sICAM-1) [46]. Furthermore, it has been recognized that hyperglycemia deteriorates vasculature via inducing endothelial activation and proinflammatory phenotype of endothelial cells, which is marked by upregulation of cell surface adhesion molecules such as ICAM-1 and vascular cell adhesion molecule-1 (VCAM-1) [40].…”
Section: Vascular Inflammationmentioning
confidence: 99%
See 1 more Smart Citation